The Factors that Influence the Readiness of Final Year Social Work Students for Industrial Training - Lukman@Zawawi, Mohamad; Nadia, Fatin; Normala, Riza; Azlini, Chik (2018)
Industrial Training is one of the compulsory course taken by final year social work students. This course is aimed for social work students to make thorough preparations before joining the real work environment. Using data obtained from online surveys, this study focused on factors influencing their readiness to undergo industrial training as well as the knowledge and skills needed. Data were obtained from 152 final year social work students subdivided into groups of 129 females and 23 males and the data was analyzed using descriptive data. The descriptive data were reported as frequency and percentage to show the student readiness. The results show that final year social work student is ready to undergo industrial training due to the most influential factors which is students received a great support from the lecturers. Therefore, it was recommended in this study that industrial training is necessary and compulsory as a requirement to fulfill the university’s curriculum.